Navigating Bullying Dynamics in Elementary Schools Amid Digital Transformation: A Systematic Literature Review - Kustiyaningsih, Ira Dwi; Gunansyah, Ganes; Puspita, Ari Metalin Ika; Purwoko, Budi; Istiq'faroh, Nurul; Mariana, Neni (Journal of Innovation and Research in Primary Education, 2025)
The rapid advancement of digital technologies in the last five years (2021–2024) has transformed the nature and dynamics of bullying among elementary school students. Bullying, which was once limited to physical and verbal aggression in school environments, has now shifted and expanded into cyberspace through social media and instant messaging platforms. This study aims to systematically review recent empirical and conceptual studies to understand the trends, risk factors, protective measures, and practical strategies for addressing bullying in elementary education. Using a Systematic Literature Review (SLR) design, ten peer-reviewed articles published between 2021 and 2024 were critically analyzed based on inclusion criteria covering relevance, credibility, and methodological rigor. The review found that the widespread availability of affordable smartphones and unsupervised internet access has escalated cyberbullying cases among young learners. Teachers remain key agents in building a safe school climate, yet their capacity must be supported by parental awareness and robust digital citizenship education. The findings also reveal that socio-emotional learning, empathy training, and technological monitoring tools are effective in mitigating bullying behaviors both offline and online. However, gaps persist in policy implementation, stakeholder synergy, and sustainable parental involvement. This study recommends that future anti-bullying programs integrate context-sensitive approaches that combine preventive education, ethical use of technology, and clear school-based regulations. The results contribute to a deeper understanding of the evolving bullying phenomenon and provide a practical reference for educators, policymakers, and researchers to develop comprehensive and adaptive strategies for fostering a bully-free learning environment in the digital age.